Locality, belonging and the social meanings of Afrikaans rhotic variation in the South Cape: from patterns of frequency towards moments of meaning - Ribbens-Klein, Yolandi (Multilingual Margins: A journal of multilingualism from the periphery, 2017)
Since Labov's ground-breaking work in 1966, there have been significant changes to the ways that social meanings of linguistic variation are perceived and studied by variationist scholars. These changes are driven by an impetus to move from a focus on the description of the social correlates of linguistic variation, towards exploring the processes involved in how linguistic variables attain indexical social meanings. This paper contributes to explorations of the social meanings of linguistic variation, and also provides current research to the dearth of studies on Afrikaans varieties. The data are from my PhD project, which investigates how people in a town in the South Cape region (Western Cape Province in South Africa) use the Afrikaans (r) to index locality, belonging, and other forms of social meanings, particularly in the context of social and geographic mobility (Ribbens-Klein, 2016). Conventional variationist sociolinguistics has focused mainly on macro-social groups, but in this paper, I choose to focus on one individual and the multiple indexical meanings of rhotic variation. I discuss three different sets of results: metalinguistic comments, the frequency use of rhotic variants, and the use of variants in interaction. This study aims to demonstrate that the frequency use of a variant is but one aspect involved in the social meanings of linguistic forms in interaction.